Against negative splitting: the case for alternative pacing strategies for elite marathon athletes in official events - Fernandes, G. D.; Maldonado, V. (arXiv e-print repository, 2023)
Objectives Negative splitting (i.e., finishing the race faster) is a tactic commonly employed by elite marathon athletes, even though research supporting the strategy is scarce. The presence of pacers allows the main runner to run behind a formation, preserving energy. Our aim is to show that, in the presence of pacers, the most efficient pacing strategy is positive splitting.